Structural conditions that leads to photoluminescence emission in SrTiO3: An experimental and theoretical approach - Longo, V. M.; Figueiredo, A. T. de; Lazaro, S. de; Gurgel, M. F.; Costa, M. G. S. [UNESP]; Paiva-Santos, C. O. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Mastelaro, V. R.; Vicente, Fábio Simões de [UNESP]; Hernandes, A. C.; Franco, R. W. A. (American Institute of Physics (AIP), 2008)
Complex cluster [TiO5 center dot V-O(z)] and [SrO11 center dot V-O(z)] (where V-O(z)=V-O(X), V-O(center dot), V-O(center dot center dot)) vacancies were identified in disordered SrTiO3 powders prepared by the polymeric precursor method, based on experimental measurements by x-ray absorption near edge structure spectroscopy. The paramagnetic complex states of [TiO5 center dot V-O(center dot)] and [SrO11 center dot V-O(center dot)] with unpaired electrons were confirmed by electron paramagnetic resonance spectroscopy. The disordered powders showed strong photoluminescence at room temperature. Structural defects of disordered powders, in terms of band diagram, density of states, and electronic charges, were interpreted using high-level quantum mechanical calculations in the density functional framework. The four periodic models used here were consistent with the experimental data and explained the presence of photoluminescence. (C) 2008 American Institute of Physics.